Representation of Muhammadiyah's Hisab Method in TVMU's Da'wah Media: Systematic Literature Review - Achmad Dzikri Fanshabi; Makroen Sanjaya; Tantan Hermansah; Muhammad Fanshoby (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Determining the beginning of the hijri month, which marks the beginning of religious observances such as the Ramadan fast and the Hajj, should ideally be carried out simultaneously in Indonesia. Differences in methods among Islamic organizations, such as Muhammadiyah and Nahdlatul Ulama, often lead to differences in timing. This study aims to examine the development of literature on Muhammadiyah's hisab method and the contribution of Islamic media to shaping public understanding of the determination of the Hijri month's beginning. The study used the Systematic Literature Review (SLR) method, following PRISMA guidelines, to include articles published between 2010 and 2025. The results show that Muhammadiyah's hisab method has evolved from a theological approach to a scientific paradigm grounded in modern astronomy, based on the principle of hisab benarki wujudul hilal (accurate crescent moon sighting). Studies of Islamic media, particularly television, show limited research specifically discussing the representation of the hisab method in religious broadcasts. The media has great potential to disseminate science-based religious literacy and strengthen public understanding of the rationality of hisab as a method for determining the Islamic calendar. This study emphasizes the importance of integrating science, religion, and Islamic media in strengthening religious awareness in the modern era.